Postoperative CSF Leak: Blood Patch—A New Avenue - Lobo, Geover; Lobo, Sarita R. J. (Asian Journal of Neurosurgery, 2023)
Introduction Cerebrospinal fluid leak (CSF) after a neurosurgical procedure is a known complication that may result in bad outcomes (1). The incidence of CSF leak varies based on the site involved; it ranges from 4 to 32% for transsphenoidal to posterior fossa procedures. The costs involved in treating postoperative CSF leaks increases exponentially that becomes a barrier in continuing optimum treatment. There are many studies that compare the different treatment modalities and even use of sealing agents but none give an algorithm of management. Our study aims at known technique that can help to treat these kinds of low-pressure CSF leaks.Materials and Methods This was a prospective study done over a period of 5 years from January 2014 to January 2019. All patients who underwent procedures in which durotomy was done were included in the study.Results A total of six patients were enrolled for the study. The duration of the study spanned 5 years from January 2014 to January 2019. All the patients after taking informed consent underwent the necessary investigations and a blood patch was done. Five of the patients the CSF stopped but in one patient it persisted. This patient again underwent investigation and under image guidance another blood patch was put after which the CSF leak stopped.Conclusion Blood patch under imaging guidance is a safe and simple technique. The success rates of cessation of CSF leaks are good. Also, it is a cost-effective method using an autograft (patient's blood).
Keywords: autograft; blood patch; CSF leak; postoperative; sealing agents